Modifying functional and nutritional properties of pulse flours and starches by roller milling and thermal processes - Qi, Jing (My University, 2025)
Functional and nutritional properties of pulse flours and starches were enhanced by controlled roller milling and thermal processes, with an emphasis on increasing resistant starch (RS) content and understanding factors that influence starch digestibility. In Chapter 1, a comprehensive review highlighted the nutritional significance of pulses, particularly dry peas, lentils, and chickpeas, which are rich in dietary fiber, slowly digestible starch (SDS), and RS. This chapter discussed how pulse-based ingredients, especially flours, can be strategically used in food applications to reduce glycemic response and enhance satiety. In Chapter 2, the molecular structure of pea starch was analyzed, and its amylose content was measured by four methods and compared with starches from maize, potato, and high amylose maize. Pea starch had ~38–40% amylose content as measured by iodine colorimetric, differential scanning calorimetry (DSC), and gel-permeation method (GPC) methods. The Concanavalin A method yielded a lower value (30.4%), suggesting the presence of clustered short branches in pea amylose. The findings highlight the importance of method selection in characterizing starch structure. Given their high amylose content, pea and high amylose maize starches were selected for the production of starch spherulites. In Chapter 3, DSC and a Parr reactor were used to investigate spherulite formation. Spherical crystalline aggregates, known as starch spherulites, were successfully formed from both starches through a controlled thermal process involving heating followed by controlled cooling. Under optimized conditions, both pea and high amylose maize starches formed B-type crystalline spherulites, highlighting the potential for scalable production and future applications in targeted nutrient delivery. In Chapter 4, dry roller milling was used to generate pulse flours from yellow peas, chickpeas, and lentils with varying cell wall integrity. Coarse-sized flours retained more intact cotyledon cell walls, leading to significantly reduced starch digestibility and higher RS levels, particularly after cooking. Chapter 5 focused on the thermal properties of dehulled pulse flours at different moisture levels using DSC. Distinct thermal behavior was observed among the flours and their components (isolated starch, protein fractions), providing fundamental knowledge for the hydration-dependent functional performance of pulse ingredients. In Chapter 6, a novel heat moisture treatment (HMT) protocol was developed and applied to pulse flours to enhance their structural and nutritional qualities. HMT led to increased RS and total dietary fiber content, altered thermal transitions, and reinforced starch crystallinity, demonstrating its potential to improve starch-protein interactions and enzymatic resistance. Chapter 7 summarized the overall conclusions and future research directions. Overall, this dissertation integrates molecular analysis, starch crystallization, flour processing, and thermal/digestibility profiling across seven chapters, advancing the understanding of how pulse starch and flour properties can be optimized for nutritional and functional applications.
Keywords: Pulse flour; Pulse starch; Heat moisture treatment; Resistant starch; Roller milling; Starch molecular structure